Challenges in the provision of digital technologies to elderly with dementia to support ageing in place: a case study of a Swedish municipality. (3rd October 2021) - Tsertsidis, Antonios
Abstract: Purpose: The aim of this paper is to identify structural problems and challenges for the delivery of digital technologies for ageing in place to elderly with dementia. Methods: To that end, I conducted a case study in a Swedish municipality. Results: The results showed that elderly with dementia are not exploiting their full potential of receiving help in the form of technology, since the four conditions of the Consumer Direction (Control and Direct services – Variety of digital technologies for ageing in place options – Information and Support – Participation in systems design) were met to a very low degree. Conclusions: I propose that the municipality in question creates a proper knowledge-sharing platform so that occupational therapists are well informed about digital technologies for ageing in place, to allow them to provide accurate information and support to elderly with dementia, resulting in a possible increase in use of technology and subsequently support the empowerment goal of Consumer Direction. I also believe, according to the findings of this study, that the module of Information and Support should be treated as the most important condition for achieving increased Consumer Direction. Implications for rehabilitation: Elderly with dementia and their relatives do not receive sufficient information about digital technologies for ageing in place (DTAP). There is not enough information regarding the available options and their use. This often denies elderly with dementia and their relatives the services they are entitled. Occupational therapists knowledge about DTAP affects the variety of options presented to elderly with dementia and their subsequent use. Once a person is diagnosed with dementia, physicians tend to suggest medicinal solutions, overlooking the dissemination of DTAP information. Thus hindering their early access to DTAP.